2016
DOI: 10.1155/2016/6353218
|View full text |Cite
|
Sign up to set email alerts
|

Functional versus Nonfunctional Rehabilitation in Chronic Ischemic Stroke: Evidences from a Randomized Functional MRI Study

Abstract: Motor rehabilitation of stroke survivors may include functional and/or nonfunctional strategy. The present study aimed to compare the effect of these two rehabilitation strategies by means of clinical scales and functional Magnetic Resonance Imaging (fMRI). Twelve hemiparetic chronic stroke patients were selected. Patients were randomly assigned a nonfunctional (NFS) or functional (FS) rehabilitation scheme. Clinical scales (Fugl-Meyer, ARA test, and modified Barthel) and fMRI were applied at four moments: bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
1
11
0
5
Order By: Relevance
“…39 Also, rehabilitation programs with functional and/or nonfunctional exercises observed decreased sparseness in fMRI activity maps, reflecting a decreased activity of the unaffected M1, decreased perilesional M1 activity. 6 These sub-acute MT modifications are consistent with previous fMRI studies that found changes in the motor cortex after many MT session. 10,14 For example, previous studies in stroke survivors suggests that the improved motor performance after 30-40 MT sessions is accompanied by increased activity of the affected M1.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…39 Also, rehabilitation programs with functional and/or nonfunctional exercises observed decreased sparseness in fMRI activity maps, reflecting a decreased activity of the unaffected M1, decreased perilesional M1 activity. 6 These sub-acute MT modifications are consistent with previous fMRI studies that found changes in the motor cortex after many MT session. 10,14 For example, previous studies in stroke survivors suggests that the improved motor performance after 30-40 MT sessions is accompanied by increased activity of the affected M1.…”
Section: Discussionsupporting
confidence: 90%
“…[34][35][36][37] In line with these findings, an increasing number of studies have suggested that increased fMRI activity of the unaffected M1, with respect to the affected M1, is associated with poorer motor recovery. 6,10,[38][39][40][41][42] On the contrary, we found significant increased focal fMRI activity in the affected M1, and decreased activity in the unaffected M1, after a single MT intervention, with a more restricted M1 activity. [43][44][45] Furthermore, increasing evidence points to a widespread recruitment of brain regions early after the stroke insult, followed by a progressive reduction in this task-related recruitment over the course of rehabilitation sessions.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The primary motor cortex (M1) is a brain region related with voluntary movement, which involves in motor function recovery. Abundant cross-sectional and longitudinal neuroimaging studies in subcortical stroke patients had confirmed that functional reorganization in the ipsilesional M1 existed (Pelicioni et al, 2016), and the resting-state functional connectivity (rsFC) between the bilateral M1s initially decreased and then it gradually increased during motor function recovery (Wang et al, 2010; Rehme et al, 2011; Zhang J. et al, 2014). …”
Section: Introductionmentioning
confidence: 99%